Analysis of Neutrophil, Leukocyte, Lymphocyte, and NLR Cell Profiles in Patients Diagnosed with Chronic Gastritis Affected by Helicobacter pylori and Non-Helicobacter pylori Infection at Dr. Soetomo Hospital in Surabaya, Indonesia - Nahdah Aulia Aziz; Manik Retno Wahyunitisari; Imam Susilo (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Helicobacter pylori (HP) is a prevalent cause of bacterial infections, particularly chronic gastritis in the human body. The diagnosis of gastritis relied on gastric biopsy examination, where inflammation is characterized by an increase in various inflammatory cells, including macrophage, neutrophil, lymphocyte, or plasma cells. Therefore, this research aimed to determine the profiles of neutrophil, leukocyte, lymphocyte, and neutrophil lymphocyte ratio (NLR) in chronic gastritis patients, distinguishing between those with Helicobacter pylori and non-Helicobacter pylori infection at Dr. Soetomo Hospital in Surabaya. This research adopted a retrospective method, using medical records for chronic gastritis patients at Dr. Soetomo Hospital between 2018 and 2022. The variables analyzed included Helicobacter pylori infections and values of neutrophil, leukocyte, lymphocyte, and NLR cells. The obtained data were subjected to analysis using descriptive statistics. The results showed that the majority of participants were females (61.9%), senior high school graduates (52.38%), and aged 45-59 (pre-elderly) (32.14%). In non-Helicobacter pylori group, the average values of neutrophil, leukocyte, lymphocyte, and NLR cells were 62.29 (SD = 12.17), 8.155 (SD = 4.02), 29.165 (SD = 12.31), and 3.68 (SD=4.865), respectively. In conclusion, females showed a propensity for chronic gastritis with Helicobacter pylori. It was observed that non-Helicobacter pylori chronic gastritis tended to have elevated neutrophil and leukocyte values. Meanwhile, Helicobacter pylori-related chronic gastritis tended to show increased lymphocyte and NLR values due to systemic inflammation. Helicobacter pylori was associated with conditions such as iron deficiency anemia, cardiovascular disease, diabetes, thyroid disease, and malnutrition.